Sesamol protects the function and structure of rat ovaries against side effects of cyclophosphamide by decreasing oxidative stress and apoptosis. Issue 7 (25th May 2022) - Talebi, Athar; Hayat, Parisa; Ghanbari, Ali; Ardekanian, Maryam; Zarbakhsh, Sam
Abstract: Aim: Chemotherapy with cyclophosphamide can damage ovaries and cause infertility in girls and women. Sesamol is a phenolic antioxidant that can protect various organs from damage. The purpose of this study was to evaluate the effects of sesamol on protecting the function and structure of rat ovaries against the side effects of a chemotherapy model with cyclophosphamide. Methods: Twenty‐four adult female Wistar rats were randomly divided into three groups: (1) normal group, without any treatment, (2) control group, immediately after receiving cyclophosphamide, 0.5% dimethyl sulfoxide (DMSO) as the solvent of sesamol was intraperitoneally injected for 14 consecutive days, (3) sesamol group, immediately after receiving cyclophosphamide, 50 mg/kg sesamol was intraperitoneally injected for 14 consecutive days. Four weeks after the last injection, superoxide dismutase (SOD) activity and malondialdehyde (MDA) levels in the ovary, anti‐Mullerian hormone (AMH) levels in the serum, number of ovarian follicles in different stages, and expression of proteins growth differentiation factor‐9 (GDF‐9), Bcl‐2, and Bax in the ovary were evaluated. Results: The results of SOD activity and MDA levels in the ovary, AMH levels in the serum, number of ovarian follicles in different stages, and expression of proteins GDF9, Bcl‐2, and Bax in the ovary were significantly more favorable in the sesamol group than the control group. Conclusions: The results suggest that sesamol may protect function and structure in the rat ovaries against side effects of the chemotherapy model with cyclophosphamide by decreasing oxidative stress and apoptosis in the ovary.